The impact of digital economy on environmental quality: Evidence from China - Zhang, Zhi; Ding, Ziqi; Geng, Yuewen; Pan, Liting; Wang, Cang (Frontiers in Environmental Science, 2023)
With the rapid development of new generation of information technology and the continuous deterioration of ecological environment, the environmental effect of digital economy has begun to receive attention. Based on panel data from 30 provinces in China during the period of 2014–2020, this study investigates the impact and mechanisms of digital economy on environmental quality using the fixed effect model and moderating effect model. The results show that the digital economy can significantly inhibit environmental pollution. The inhibitory effect of digital economy shows obvious regional heterogeneity, which is the strongest in the west, followed by the east, and the weakest in the center. The economic development level and income distribution inequality play positive and negative roles in regulating the negative linkage between digital economy and environmental pollution, respectively. The government should implement a differentiated strategy to promote the comprehensive development of digital economy and maximize its environmental effects, accelerate the integrated development of urban and rural economies through inclusive growth, and optimize the moderating effect of economic development level and income distribution inequality.